Optimization Of Carbon Nanotubes Formation And The Role Of Water Vapor In Catalytic Decomposition Of Methane - Lee , Kim Yang (2011)

(untitled)
Nanotiub karbon (CNT) disintesis menggunakan mangkin CoOx-MoOx/Al2O3 melalui penguraian metana dalam sistem reaktor tiub kuarza mendatar.